Hadith Perspective on Cancel Culture and the Tendency to Judge on Social Media - Ainy, Siti Dzurrotul; Zakka, Fathoniz (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The cancel culture phenomenon on social media encourages people to quickly judge and boycott individuals without an adequate clarification process, which is contrary to Islamic teachings regarding justice and information verification (tabayyun). This research aims to examine cancel culture from a hadith perspective, especially in the context of judgment ethics in the digital era. Using qualitative methods with a content analysis approach to several hadiths, this research found that the Prophet's teachings recommend caution in disseminating information and prohibition of making judgments without a clear basis. These hadiths teach that a Muslim must try to understand the context and facts thoroughly before passing judgment or acting. Analysis shows that actions in cancel culture often violate these principles, by prioritizing prejudice, emotion and social pressure over fair and wise judgment, as recommended by the hadith. This research contributes to providing guidance for the community to use social media wisely in accordance with Islamic teachings, as well as assisting authorities and religious institutions in formulating ethical guidelines for the use of social media in the midst of the rampant cancel culture phenomenon.